“How I Do It: High Flow, Non-invasive ventilation and Awake (non-intubation) Proning in Covid-19 Patients with Respiratory Failure” (2020)
The Covid 19 pandemic will be remembered for the rapidity with which it spread, the morbidity and mortality associated with it and the paucity of evidence-based management guidelines. One of the major concerns of hospitals was to limit spread of infection to health care workers. Since the virus is spread mainly by respiratory droplets and aerosolized particles, procedures which may potentially disperse viral particles, the so called “aerosol-generating procedures” or AGPs were avoided whenever possible. Included in this category were non-invasive ventilation (NIV), high flow nasal cannula (HFNC) and awake (non-intubated) proning. Accordingly, at many health care facilities, patients who had increasing oxygen requirements were emergently intubated and mechanically ventilated to avoid exposure to AGPs. With experience, clinicians realized that mortality of invasively ventilated patients was high and it was not easy to extubate many of these patients. This raised the concern that HFNC and NIV were being underutilized to avoid intubation and to facilitate extubation. In this article, we attempt to separate fact from fiction and perception from reality pertaining to the aerosol dispersion with NIV, HFNC and AP. We describe precautions that hospitals and health care providers must take to mitigate risks with these devices. Finally, we take a practical approach in describing how we use the three techniques, including the common indications, contraindications and practical aspects of application.